Acute therapy of the most common primary headaches - Skorupan Nikolina (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Primary headaches are clinical syndromes of unknown etiology, with headache being the key feature. The most common primary headaches are tension type headache, migraine and cluster headache. Causes of primary headaches are poorely understood, therefore the treatment is mostly symptomatic. The short-term treatment goal is to achieve rapid pain relief which can be achieved using acute drug therapy. Unsuccessful acute drug therapy can lead to acute medications overuse and increased risk of medication overuse headache (MOH). MOH is difficult to treat and relaps rates are high. Drugs for acute pharmacological therapy of primary headaches include nonopioid analgesics, migraine specific medications and miscelanous symptomatic drugs. Their efficacy decreases with the increase of frequency and severity of headache attacks. Therefore efficacy must be the key feature when choosing the most suitable acute medication. Patients should be advised to take acute medications as early as possible during their headache attacks, unless at risk for MOH. The acute medications must be taken before the onset of central sensitization, because they can prevent but not abbort central sensitization.